Faktor gangguan perhatian dalam pemerolehan bahasa pada anak down syndrome:studi kasus Sutan dan Peli di SLB negeri 1 Padang - Anita Angraini Lubis; Muttaqin Kholis Ali (JRTI (Jurnal Riset Tindakan Indonesia), 2022)
This research is a case study on two students of SLB Negeri 1 Padang. The methods and techniques used in this research are, at the data collection stage using the rules of observation and analysis, case studies, natural observation, and listening. In addition, the listening-engagement technique (SLC) is also used, free-engage-in conversation (SBLC) listening, recording, taking notes, recording with a speech analyzer, flash cards, articulatory matching method for the data analysis stage, and formal and informal presentation methods for the presentation stage. results of data analysis. The source of data in this study is the source of oral data taken from the speech of the Down syndrome sufferer, namely P and S. Based on the data analysis that has been done, P is able and understands the use of affixation from the description of the picture card (FC) shown to him, there are 6 types of affixation produced by P and as many as 11 forms are said by P. In contrast to S who is still unable to to pronounce affixation at all, because the sylabas that can be pronounced tend to only be final sylabas on each picture card (FC) submitted to S. The factors that influence the difference in verbal abilities of DS sufferers are P and S, including attention disorders (understanding), memory disorders, emotional and feeling disorders, as well as psychological factors.